2021
DOI: 10.1136/bmjdrc-2020-001646
|View full text |Cite
|
Sign up to set email alerts
|

Sex, diabetes status and cognition: findings from the study of longevity in diabetes

Abstract: IntroductionWomen comprise two-thirds of people with dementia, making female sex a significant dementia risk factor. Both type 1 diabetes (T1D) and type 2 diabetes (T2D) are known dementia risk factors with an increasing global incidence. Understanding whether subtle sex differences persist in cognitive function prior to dementia in the context of diabetes may help elucidate the magnitude of sex effects on dementia risk.Research design and methodsWe examined cross-sectional data from the Study of Longevity in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…In our examination of cognition and age-based cognitive decline, we find clear evidence of a negative, statistically significant relationship between diabetes status and cognition for both males and females. These findings echo earlier work in the field (Chatterjee et al, 2016; Elias et al, 2005; Logroscino et al, 2004; Maggi et al, 2009; Moran et al, 2021; Okereke et al, 2008; Roberts et al, 2014) and emphasize the importance of managing the social, behavioral, and clinical predictors of type 2 diabetes mellitus, regular blood glucose/A1C screenings, and proper management of type 2 diabetes across the life course. While these interventions are likely essential to improving general health and cognition among older adults at large, the sex-based differences observed in this study necessitate both direct attention and further investigation.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…In our examination of cognition and age-based cognitive decline, we find clear evidence of a negative, statistically significant relationship between diabetes status and cognition for both males and females. These findings echo earlier work in the field (Chatterjee et al, 2016; Elias et al, 2005; Logroscino et al, 2004; Maggi et al, 2009; Moran et al, 2021; Okereke et al, 2008; Roberts et al, 2014) and emphasize the importance of managing the social, behavioral, and clinical predictors of type 2 diabetes mellitus, regular blood glucose/A1C screenings, and proper management of type 2 diabetes across the life course. While these interventions are likely essential to improving general health and cognition among older adults at large, the sex-based differences observed in this study necessitate both direct attention and further investigation.…”
Section: Discussionsupporting
confidence: 82%
“…They find lower prevalence of cognitive impairment among women with diabetes relative to their male counterparts in their analyses of Action for Health in Diabetes data, a cross-sectional, clinical dataset (Espeland et al, 2018). Most recently, Moran et al (2021) examine the moderating role of sex in the relationship between diabetes status and cognition in mid-late life. Here, they use cross-sectional data from the Study of Longevity in Diabetes and find that, relative to men, women maintain better midlife cognition independent of diabetes status (Moran et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study showed that women with diabetes are more likely to develop all-cause dementia than men, but not by dementia subtypes [ 10 ]. However, other studies observed no interaction between sex and diabetes on dementia [ 11 13 ]. Thus, the sex-specific association in the relationship between T2DM and dementia subtypes may need to be further explored.…”
Section: Introductionmentioning
confidence: 93%